(3OjhGf GdbWGeis - (3GdbWGej , YejQ Hf Tjje Hf YeQh Hf YHGO GdJZdHj, CHh SYjO,J (B130 (3g` s ((3GHh GdHQcGJ GdeQcH CHj GdaJM Hf GdeHGQc Hf ehghH Hf Zfjeg Hf ZGdH s)
(3ChdgG (B:s
(3bGd CHh YejQ hjbGd GdbWGei bhdg jMWgf LGfHkG aLGfHkG MW GdbWGei GdbWG GdbhGQjG s
(3BNQgG (B:s
(3GdPi jMO GdMOjO Hg GdPi jSejg GdfGS eTMg JbGd CSWeh Scjfce Ci CMOhgG Je TYQ GdbWGei hGdMeO ddg MeO GdTGcQjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B264s
Keywords: (3GdCOHs